Role of Theory of Planned Behavior in Interpreting Sustainable Consumption Behavior : A Meta-Analysis - Kumar, Satinder; Jain, Esha (Indian Journal of Marketing, 2024)
Purpose : This study consolidated the existing literature on the theory of planned behavior and investigated the factors that most significantly impacted the intention to sustain consumption behavior. The study also examined whether environmental concern and materialism could be regarded as valid direct predictors. Methodology : Meta-analysis was conducted to evaluate and validate bivariate relationships between the theory of planned behavior antecedents and its relationship with the â€œintention to sustainable consumption.â€ Environmental knowledge, concern, and materialism were also examined as probable antecedents to the â€œintention to sustainable consumption behavior.â€ Findings : All the variables significantly influenced the â€œintention to sustainable consumption behavior.â€ Environmental concern was found to be moderated by the product consumed. The study also identified the intention-behavior gap and recommended future research to explore the factors contributing to this gap. Practical Implications : Marketers should direct their efforts toward building a positive consumer attitude toward sustainable products by focusing on long-term planning to establish the product in the green category. Initially, marketers should focus on consumers who are less materialistically driven. Originality : We provided sufficient evidence that environmental concern and materialism should be considered direct indicators for predicting â€œintention to sustainable consumption behavior.â€